Medical Therapy of Endogenous Cushing’s Syndrome with Steroidogenesis Inhibitors: Treatment Rationale, Available Drugs, and Therapeutic Effects - Detomas, Mario; Deutschbein, Timo; Altieri, Barbara (Experimental and Clinical Endocrinology & Diabetes, 2024)
Endogenous Cushing’s syndrome (CS) is a rare disease characterized by a glucocorticoid excess. If inadequately treated, hypercortisolism can lead to increased morbidity and mortality. Surgical removal of the underlying tumor is the first-line treatment but is sometimes not feasible or even contraindicated. Additionally, in cases with severe CS, rapid control of hypercortisolism may be required. In these scenarios, steroidogenesis inhibitors represent a therapeutic alternative to surgery. Over the last years, the knowledge of the broad therapeutic effects of steroidogenesis inhibitors per se and the number of available drugs have increased. However, large comparative studies are still lacking. Accordingly, the decision on which drug to be used in a certain patient or clinical setting may be difficult. This review aims to summarize the main characteristics of steroidogenesis inhibitors.
Keywords: etomidate; hypercortisolism; ketoconazole; levoketoconazole; medical therapy; metyrapone; mitotane; osilodrostat